Pregnancies Complicated by Familial Hypertriglyceridemia: A Case Report - Cao, Suzanne; Dao, NhuChi; Roloff, Kristina; Valenzuela, Guillermo J. (American Journal of Perinatology Reports, 2018)
Background Although rare, familial hypertriglyceridemia can cause acute and life-threatening complications in pregnancy.Cases The first patient's pregnancy was complicated by multiple admissions for pancreatitis due to hypertriglyceridemia and noncompliance with gemfibrozil. In her second pregnancy, she was compliant with gemfibrozil and only experienced pancreatitis episodes toward the end of pregnancy. The second patient had diabetes mellitus and familial hypertriglyceridemia. She required multiple hospitalizations for diabetic ketoacidosis secondary to insulin noncompliance. In both pregnancies, she was compliant with gemfibrozil and had no complications related to hypertriglyceridemia.Conclusion Treatment with gemfibrozil in pregnancies complicated by hypertriglyceridemia may prevent complications without adverse maternal or fetal effects and could be considered in treating pregnant patients with severe hypertriglyceridemia. These cases also demonstrate the importance of medication compliance in the prevention of poor outcomes.
Keywords: familial hypertriglyceridemia; pancreatitis; gemfibrozil; preterm delivery; fetal demise